Cultura e(m) telecolaboração: uma análise de parcerias de teletandem institucional - Zakir, Maisa de Alcântara [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation presents an exploratory ethnographic study that investigates telecollaborative partnerships among students of a public university in Brazil and of a private university in the United States. The research study is part of the project entitled Teletandem: Transculturality in Online Communication in Foreign Languages via Webcam and is related to the topic ways of understanding the partner's culture and its impacts on the learning process and the relationship between partners. The study aims at investigating the role of culture in the context of an institutional teletandem partnership. Thus, the specific objectives are: identifying the participants' conceptions of culture in activities proposed in a virtual learning platform and understanding how culture emerges in the dynamics of teletandem interactions. The participants were in contact with each other during part of the spring semester of 2012 in ten interactions conducted via Skype, with audio, video and chat resources. The last five teletandem sessions were recorded and the transcriptions are the main data of this study. Besides the interactions, other activities are part of the corpus: (a) texts that were written and published by the students in a virtual learning platform (user's profile; narratives about the teletandem interactions; posts in a virtual discussion forum) and (b) handwritten texts that were produced by the students of the American university at the end of the semester. Considering the principle of dialogism from the relationality of the self and the other, and the production of meaning as part of the social activities of students, data are interpreted under the perspective of the theoretical methodological principles of what is called in Brazil Dialogic Discourse Analysis. Thus, the different texts produced by the participants will be deemed to give more elements to interpret data and, therefore, to investigate linguistic, social and ...

Esta tese apresenta um estudo exploratório e de natureza etnográfica, que investiga parcerias telecolaborativas entre alunos de uma universidade pública no Brasil e de uma universidade privada nos Estados Unidos. A pesquisa integra o projeto Teletandem e transculturalidade na interação on-line em línguas estrangeiras por webcam, relacionando-se ao eixo temático modos de compreender a cultura do parceiro e seus impactos sobre a aprendizagem e sobre a relação. A pesquisa tem como objetivo central investigar o lugar da cultura no contexto de uma parceria de teletandem institucional. Para isso, os objetivos específicos são: identificar concepções de cultura em atividades realizadas pelos participantes da pesquisa em uma plataforma virtual de aprendizagem e compreender de que modo a cultura emerge na dinâmica das interações de teletandem. Os alunos participantes da pesquisa estiveram em contato durante parte do primeiro semestre de 2012 em dez interações realizadas via Skype e contaram com recursos de áudio, vídeo e mensagens escritas. Foram gravadas as cinco últimas sessões de teletandem, cujas transcrições constituem os dados focais deste estudo. Além das interações, fazem parte do corpus: (a) os textos escritos pelos alunos e publicados em uma plataforma virtual de aprendizagem (perfil; narrativas sobre as interações de teletandem; postagens em um fórum virtual de discussão) e (b) os textos produzidos em sala de aula pelos alunos da universidade estadunidense participante. Considerando o princípio do dialogismo a partir da premissa da constituição do eu pelo outro, e a produção de sentidos como parte integrante das atividades sociais dos participantes da pesquisa, os dados são interpretados à luz dos princípios teórico-metodológicos da Análise Dialógica do Discurso. Assim, os textos de diferentes materializações produzidos pelos participantes são considerados para fundamentar a...
Keywords: Linguistica aplicada; Professores de linguas - Formação; Linguagem e cultura; Cultura; Análise do discurso; Dialogismo (Análise literária); Ensino a distância - Ensino auxiliado por computador; Applied linguistics